Emerging treatments for metastatic breast cancer: update from 2012. (January 2013) - Thanopoulou, Eirini; Schiavon, Gaia; Allen, Mark; Johnston, Stephen RD
SUMMARY Metastatic breast cancer is still incurable and, thus, the goals of treatment focus on optimal palliation and extending the quality of survival through effective anticancer therapies that have acceptable toxicities. Cancer progression and development of drug resistance are dynamic processes of clonal adaptation both to evolving microenvironments with acquired tumor mutations and to continuous drug exposure. Preclinical research is constantly improving our understanding of breast cancer biology at a molecular level and, as such, current clinical research is focusing on designing trials with new targeted drugs and their appropriate combinations with endocrine and chemotherapy agents. In this review, we provide an overview of the most recent advances in the metastatic breast cancer setting by clinical subtype, giving emphasis to recently concluded or ongoing trials that have the potential to challenge and change current clinical practice.